1997
DOI: 10.1109/50.554389
|View full text |Cite
|
Sign up to set email alerts
|

An optical filter of adjustable finesse using an amplified fiber ring resonator

Abstract: We consider an optical filter constructed from a simple ring resonator with two electro-optical directional couplers and a fiber amplifier in the ring. By adjusting the coupling coefficient of the electro-optical directional couplers, the finesse of this optical filter can be controlled over a specified range. The variation in the insertion loss of the optical filter can be overcome by adjusting the gain of the fiber amplifier simultaneously. This paper analyzes theoretically the performance of the optical fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This property has been used in designing a RR with tuning finesse and constant loss. 3 In summary, it has been shown that device performance depends on the value of ͉H͉.…”
Section: Implementation Of the Rrgb Routermentioning
confidence: 99%
See 1 more Smart Citation
“…This property has been used in designing a RR with tuning finesse and constant loss. 3 In summary, it has been shown that device performance depends on the value of ͉H͉.…”
Section: Implementation Of the Rrgb Routermentioning
confidence: 99%
“…Several applications of RR's, including routers in self-routing frequency-division multiple-access networks, 1 as filters in optical frequency-division multiplexing transmission systems, [2][3][4] and as converters from frequency-shift to amplitude-shift keying modulation, 5 have been reported. RR's have also been used with Bragg gratings 2,6 as tuning filters.…”
Section: Introductionmentioning
confidence: 99%
“…Tunability of these filters is an essential element of their work, which is to be carried out, at least, in modern wavelength division multiplexing (WDM) systems with the carrier spacing of less than 50 GHz [8]. Optical filters based on the FORR may be tuned using various methods such as changing of a coupler ratio [9], a Sagnac phase-shift [1], a finesse of a resonator [10], and phase matching conditions of a loop resonator [11]. In a recent work [12], a highbirefringence (HBF) fibre ring resonator with an inline reflector has been proposed where a piece of single-mode fibre is replaced with a piece of HBF in order to obtain a narrowband filters based on Vernier effect for the use in single-frequency fibre lasers.…”
Section: Introductionmentioning
confidence: 99%